Answer:
f(x) = -(x-3)^2 + 4
Step-by-step explanation:
(h; k) are the coordinates of the vertex.
On the graph are (3, 4), therefore we have:
f(x) = a(x-3)^2 + 4
We have the x- intercept (1,0) -> x=1; y=0.
Substitute them into the equation:
0 = a(1 - 3)^2 + 4
0 = a(-2)^2 + 4
4a + 4 = 0 | -4
4a = -4 |-4
a = -1
So, we have the answer:
f(x) = -(x-3)^2 + 4
Answer:
1) Place the compass point at the vertex of the angle and open it to any width. Draw an arc that intersects of the sides of the angle.
2) Place the compass point at the one of the intersection points. Place the pencil at the other intersection point. This sets the compass with.
3) Draw an arc inside the angle.
4) Move the compass point to the intersection point on the other side of the angle being sure to keep the compass width the same. Draw a second arc inside the angle.
5) Make a point where the 2 arcs intersect the angle. Use a straight edge to draw a ray from the vertex of the angle through the point.
Sorry but there are no photos or anything, please post a photo or something so I can answer your question!